Remote sensing to support the monitoring of Citrus tristeza virus (CTV) infected areas - Santoro F.; Gualano S.; Djelouah K.; Guario A.; D'Onghia A.M. (Citrus tristeza virus and Toxoptera citricidus: a serious threat to the Mediterranean citrus industry, 2009)
Citrus tristeza virus (CTV) is the most destructive pathogen in Citrusspp.. It is therefore necessary to promptly identify suspected infected trees on a large scale by the use of satellite imaging. To this aim, the vegetation indices of CTV-infected and CTV-negative citrus trees were preliminarily investigated in order to provide the tree spectral signature detected in the field by the HandHeld Post Dispersive Spectrometer. The study was carried out in selected commercial groves ('Precoce di Massafra' clementine and 'Navelina' orange) located in the CTV foci area, both showing a high CTV infection rate. The trees were previously tested by serological (DTBIA and ELISA) and molecular (PCR) tools to assess the virus presence. The preliminary results highlighted a difference in the spectral signatures of CTV-infected and CTV-free trees, allowing a discrimination of the canopy stress level based on the vegetation indices properly estimated. Further variation was recorded according to the species. Based on these results, the use of vegetation indices from highresolution multispectral satellite imaging may represent a valid tool backing up the pathogen monitoring in wide areas.